Exploring triacylglycerol biosynthetic pathway in developing seeds of Chia (Salvia hispanica L.): a transcriptomic approach. - Sreedhar R V (PLoS ONE, 2015)
Chia (Salvia hispanica L.), a member of the mint family (Lamiaceae), is a rediscovered crop with great importance in health and nutrition and is also the highest known terrestrial plant source of heart-healthy omega-3 fatty acid, alpha linolenic acid (ALA). At present, there is no public genomic information or database available for this crop, hindering research on its genetic improvement through genomics-assisted breeding programs. The first comprehensive analysis of the global transcriptome profile of developing Salvia hispanica L. seeds, with special reference to lipid biosynthesis is presented in this study. RNA from five different stages of seed development was extracted and sequenced separately using the Illumina GAIIx platform. De novo assembly of processed reads in the pooled transcriptome using Trinity yielded 76,014 transcripts. The total transcript length was 66,944,462 bases (66.9 Mb), with an average length of approximately 880 bases. In the molecular functions category of Gene Ontology (GO) terms, ATP binding and nucleotide binding were found to be the most abundant and in the biological processes category, the metabolic process and the regulation of transcription-DNA-dependent and oxidation-reduction process were abundant. From the EuKaryotic Orthologous Groups of proteins (KOG) classification, the major category was "Metabolism" (31.97%), of which the most prominent class was 'carbohydrate metabolism and transport' (5.81% of total KOG classifications) followed by 'secondary metabolite biosynthesis transport and catabolism' (5.34%) and 'lipid metabolism' (4.57%). A majority of the candidate genes involved in lipid biosynthesis and oil accumulation were identified. Furthermore, 5596 simple sequence repeats (SSRs) were identified. The transcriptome data was further validated through confirmative PCR and qRT-PCR for select lipid genes. Our study provides insight into the complex transcriptome and will contribute to further genome-wide research and understanding of chia. The identified novel UniGenes will facilitate gene discovery and creation of genomic resource for this crop.